Pathological changes in pulmonary circulation in carbon tetrachloride (CCl4)-induced cirrhotic mice. - Mita Das; Marjan Boerma; Jessica R Goree; Elise G Lavoie; Michel Fausther; Igor B Gubrij; Amanda K Pangle; Larry G Johnson; Jonathan A Dranoff (PLoS ONE, 2014)
Rationale Lack of an experimental model of portopulmonary hypertension (POPH) has been a major obstacle in understanding of pathophysiological mechanisms underlying the disease. Objective We investigated the effects of CCl4-mediated cirrhosis on the pulmonary vasculature, as an initial step towards an improved understanding of POPH. Methods and results Male C57BL/6 mice received intraperitoneal injection of either sterile olive oil or CCl4 3 times/week for 12 weeks. Cirrhosis and portal hypertension were confirmed by evidence of bridging fibrosis and nodule formation in CCl4-treated liver determined by trichrome/picrosirius red staining and an increase in spleen weight/body weight ratio, respectively. Staining for the oxidative stress marker, 4-hydroxynonenal (4-HNE), was strong in the liver but was absent in the lung, suggesting that CCl4 did not directly induce oxidative injury in the lung. Pulmonary acceleration time (PAT) and the ratio of PAT/pulmonary ejection time (PET) measured by echocardiography were significantly decreased in cirrhotic mice. Increase in right ventricle (RV) weight/body weight as well as in the weight ratio of RV/(left ventricle + septum) further demonstrated the presence of pathological changes in the pulmonary circulation in these mice. Histological examination revealed that lungs of cirrhotic mice have excessive accumulation of perivascular collagen and thickening of the media of the pulmonary artery. Conclusion Collectively, our data demonstrate that chronic CCl4 treatment induces pathological changes in pulmonary circulation in cirrhotic mice. We propose that this murine cirrhotic model provides an exceptional tool for future studies of the molecular mechanisms mediating pulmonary vascular diseases associated with cirrhosis and for evaluation of novel therapeutic interventions.